A Review: Improving Generic Science Skills through Interactive Web-Based Modern Physics Learning Media with PjBL Model - Aris Doyan; Susilawati; Ahmad Harjono; Syarful Annam; Muhammad Ikhsan; Nuraini Rachma Ardianti; Syamsul Hakim (Jurnal Penelitian Pendidikan IPA, 2025)
Generic science abilities are abilities that students must have so that the knowledge and skills obtained in the learning process can be applied in everyday life and answer the challenges of an increasingly developing era. Generic science skills can be facilitated through learning with a Project Based Learning (PjBL) model and using of interactive web. This research aims to identify and analyze research trends of improving generic science skills through interactive web-based modern physics learning media with PjBL model. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2015-2024 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis show that research trend indexed by Google Scholar from 2015 to 2024 has experienced a fluctuating increase. Research trend with an increase in the number of publications from 2015 to 2018. However, in 2019 and 2022 the research trend on the generic science ability in learning has decreased from the previous year and the research trend increase again in 2023. There are many documents in the form of articles, proceedings, book chapters and edited books that discuss research improving generic science skills through interactive web-based modern physics learning media with PjBL model. Key words that are often used in research of generic science are critical thinking, e module, science learning, PBL, etc.